2007
DOI: 10.1016/j.juro.2007.07.014
|View full text |Cite
|
Sign up to set email alerts
|

An Independent Analysis of Flexible Cystoscope Repairs and Cost

Abstract: Olympus cystoscopes require repair every 2 to 3 years and they appear to be durable. The distal deflection tip, specifically the outer bending rubber, is the most common site of flexible cystoscope damage. Although it appears that significant improvements have been made to the deflection apparatus, the number of repairs to other areas has not changed significantly with time. Improvements in form and function of the distal tip, the hand control segment and the fiberoptic bundles may enhance the durability of fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…In a retrospective study, Canales et al showed that flexible cystoscopes required repair every 2 to 3 years over a four year study period. However, they did not report the number of uses before repair and the mechanism of damage [18]. And finally, Fuselier and Mason found that 7 cystoscopes were damaged over a two year study period including approximately 2,000 procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study, Canales et al showed that flexible cystoscopes required repair every 2 to 3 years over a four year study period. However, they did not report the number of uses before repair and the mechanism of damage [18]. And finally, Fuselier and Mason found that 7 cystoscopes were damaged over a two year study period including approximately 2,000 procedures.…”
Section: Discussionmentioning
confidence: 99%
“…For the latter procedure, this requires a dedicated place with video equipment as well as cystoscopes and graspers. These instruments are fragile and have to be disinfected after each procedure, which may limit the number of procedures due to their availability [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Flexible cystoscopy is a commonly performed diagnostic and therapeutic urological procedure which carries significant financial burden to health systems. 1 Urological departments typically perform flexible cystoscopy in specialised endoscopy units, day procedure units or operating theatres with additional health care professional staffing and cost requirements. Since their invention, double-J ureteric stents have been a critical tool in urological practice and their insertion and removal is one of the most common procedures performed.…”
Section: Introductionmentioning
confidence: 99%
“…An independent analysis of Olympus ® fibreoptic flexible cystoscope repairs undertaken by Canales et al showed that the most common damage on a flexible cystoscope is the outer bending rubber on distal deflection tip. 13 This is not unexpected as this part of the flexible cystoscope is constantly subjected to enormous amount of stress especially when it is deflected during cystoscopy. As for our flexible cystoscopes, leaks and cracked lens were the most common issues observed.…”
Section: New Scope Each Timementioning
confidence: 99%